Atlantic Ocean Heat Transport Enabled by Indo‐Pacific Heat Uptake and Mixing. Issue 23 (11th December 2019) - Holmes, Ryan M.; Zika, Jan D.; Ferrari, Raffaele; Thompson, Andrew F.; Newsom, Emily R.; England, Matthew H.
Abstract: The ocean transports vast amounts of heat around the planet, helping to regulate regional climate. One important component of this heat transport is the movement of warm water from equatorial regions toward the poles, with colder water flowing in return. Here, we introduce a framework relating meridional heat transport to the diabatic processes of surface forcing and turbulent mixing that move heat across temperature classes. Applied to a (1/4)° global ocean model the framework highlights the role of the tropical Indo‐Pacific in the global ocean heat transport. A large fraction of the northward heat transport in the Atlantic is ultimately sourced from heat uptake in the eastern tropical Pacific. Turbulent mixing moves heat from the warm, shallow Indo‐Pacific circulation to the cold deeper‐reaching Atlantic circulation. Our results underscore a renewed focus on the tropical oceans and their role in global circulation pathways. Key Points: Heat budget analysis reveals links between meridional and diathermal ocean heat transports Large fraction of Atlantic northward heat transport is sourced from eastern tropical Pacific heat uptake Turbulent mixing transfers heat from warm shallow Indo‐Pacific circulation to cold deep‐reaching Atlantic circulation